Improving Ergonomics and Quality As surance in Actuator Production: An Enhanced Component Supply Approach for Pick & Place Robots - Alverstrand, Marcus; Trogen, Edward (My University, 2023)
Over the past few decades, there has been a substantial increase in the automation of manual jobs. Automation gives the possibility of increasing productivity and reducing labor costs. Despite these benefits, some industries struggle to automate their processes. One of the big obstacles for automated systems is the orientation of small, irregularly shaped components. The purpose of this thesis is to specify an improved solution for supplying a pick & place robot with incoming components during the assembly process. To study this, automated palletizing solutions were developed and tested using a UR3e robot along with a Robotiq wrist camera. Some manual processes were also developed for components that had trouble being iden tified by the camera during testing. The tests showed that it is in fact very hard to automate processes where small and irregularly shaped components are involved. Implementing automated solutions can create lengthy setup and cycle times, compared to manual work, and increase costs. It was also shown that the camera used is not strong enough for identifying the small and complex requirements of the components. In the case of Cochlear, a completely new vision system is needed in order to automate the material feeding of components to the assembly.
Keywords: Material Handling, Automation, Small Components